Pengaruh Employee Engagement Terhadap Turnover Intention Perawat Dari RS Grestelina Makassar Tahun 2022 - Nur Miftahul Janna; Mene Paradilla (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Turnover intention is the degree of tendency of the attitude that employees have to find a new job elsewhere or the existence of a plan to leave the company within a predetermined period. A high turnover rate will have a negative impact on the organization, including the loss of quality human resources, an increase in human resource costs in the form of training costs that have been invested in employees who leave to the cost of recruitment and retraining and the loss of work culture values in the company. One way to reduce the high turnover intention of the workforce by increasing the positive attachment of individual employees to the organization and organizational value is called Employee Engagement. This study aims to analyze the effect of employee engagement on the turnover intention of nurses at Grestelina Hospital Makassar. The type of research carried out is quantitative research using observational studies with a cross sectional study design. The sample in this study used a total sampling of 188 nurses at Grestelina Makassar Hospital. The results showed that the turnover intention of nurses at Grestelina Hospital was 50.5% with the most influential dimension on turnover intention from the employee engagement variable, namely dedication with a sig value of 0.045. The conclusion that employee engagement of 0.019<0.05 with a value of 12.6%, had a significant effect on the turnover intention of nurses at Grestelina Hospital Makassar. Researchers can then conduct research with qualitative methods to dig deeper into research variables.